Reducing dynamical electron scattering reveals hydrogen atoms. Issue 1 (6th December 2018) - Clabbers, Max T. B.; Gruene, Tim; van Genderen, Eric; Abrahams, Jan Pieter
Abstract : Experimental and computational reduction of dynamical electron scattering allows for visualizing of individual hydrogen atoms. Abstract : Compared with X‐rays, electron diffraction faces a crucial challenge: dynamical electron scattering compromises structure solution and its effects can only be modelled in specific cases. Dynamical scattering can be reduced experimentally by decreasing crystal size but not without a penalty, as it also reduces the overall diffracted intensity. In this article it is shown that nanometre‐sized crystals from organic pharmaceuticals allow positional refinement of the hydrogen atoms, even whilst ignoring the effects of dynamical scattering during refinement. To boost the very weak diffraction data, a highly sensitive hybrid pixel detector was employed. A general likelihood‐based computational approach was also introduced for further reducing the adverse effects of dynamic scattering, which significantly improved model accuracy, even for protein crystal data at substantially lower resolution.